Risk Assessment and Legal Countermeasures for Copyright Infringement in the Cultural Industry under the Background of Digital Age - Yang, Liu; Liang, Yuanyuan; Zhang, Fangyuan (Journal of Artificial Intelligence and Information, 2025)
Digital technology has promoted the innovative development of the cultural industry, and new forms of copyright carriers have emerged, giving rise to the new concept of digital copyright. However, it has also increased the risk of copyright infringement. This article analyzes the main impact of digitization on copyright, explores the current problems faced in legal norms and technical management regulations, and proposes targeted legal countermeasures and management suggestions to address the complex situation of copyright protection in the digital age.